2023
DOI: 10.3390/ijms24043249
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Bioactive Nanoparticles for Bone Tissue Applications

Abstract: Research in nanomaterials with applications in bone regeneration therapies has experienced a very significant advance with the development of bioactive mesoporous nanoparticles (MBNPs). These nanomaterials consist of small spherical particles that exhibit chemical properties and porous structures that stimulate bone tissue regeneration, since they have a composition similar to that of conventional sol–gel bioactive glasses and high specific surface area and porosity values. The rational design of mesoporosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 153 publications
0
6
0
Order By: Relevance
“…Based on the amount of Ca, Si, P, and Li ions released, Li-MNPs are expected to influence the cellular regenerative response, as these ions have been shown to significantly stimulate stem cell and endothelial cell functions. 37 Therefore, the biological effects of Li-MNPs were investigated using hDPSCs, resident cells on the dental pulp susceptible to bacterial infection, which play an important role in tissue regeneration. 38,39 We first identified these cells using flow cytometry and immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the amount of Ca, Si, P, and Li ions released, Li-MNPs are expected to influence the cellular regenerative response, as these ions have been shown to significantly stimulate stem cell and endothelial cell functions. 37 Therefore, the biological effects of Li-MNPs were investigated using hDPSCs, resident cells on the dental pulp susceptible to bacterial infection, which play an important role in tissue regeneration. 38,39 We first identified these cells using flow cytometry and immunofluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…[33] We selected the gel-sol method to synthesize MBG nanoparticles due to their good bone regeneration and integration properties. [34][35][36] Both TEM images and scanning electron microscopy (SEM) images showed uniform and highly ordered mesoporous spheres with a particle size of ≈500 nm (Figure 1B,C). The X-ray diffraction pattern exhibited a broad peak at 24°, indicative of the amorphous structure of MBG (Figure S1C, Supporting Information).…”
Section: Design and Construction Of Smb6 Biomimetic Bi-layer Cranium-...mentioning
confidence: 99%
“…Thus, it is essential to create an effective drug delivery system that can sustain stable and suitable concentrations of quercetin in targeted tissues for clinical use. Recently, MBG nanoparticles are being considered as potential drug carriers for bone defect sites, due to their high porosity, specific surface area, and strong ability to stimulate bone tissue regeneration [ 21 ]. Furthermore, researches indicated that when MBG was utilized as a drug delivery system for bone repair, it did not elicit an unfavorable immune response in macrophages [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%